La déviance dans l’œuvre de Charles Fourier : un symptôme de la société civilisée - Mariana Saad (Cahiers Victoriens et Edouardiens)
This article shows that Charles Fourier considers the world around him with the eyes of a physician and that he criticises the way society produces its own deviants which he sees as so many signs of malfunctioning. Resorting to patterns inspired from Vitalist medecine, Fourier demonstrates that society exerts an oppressive control over individuals and generates imbalance and suffering at every possible level. The novelty of these views lies in the way Fourier transposes a « pathological » analysis of the economic sphere to the political and private spheres.